High Prevalence of Genetically Related Clostridium Difficile Strains at a Single Hemato-Oncology Ward Over 10 Years - Waker, Edyta; Ambrozkiewicz, Filip; Kulecka, Maria; Paziewska, Agnieszka; Skubisz, Karolina; Cybula, Patrycja; Targoński, Łukasz; Mikula, Michał; Walewski, Jan; Ostrowski, Jerzy (Frontiers in Microbiology, 2020)
Aims Clostridium difficile (C. difficile) infection (CDI) is the main cause of healthcare-associated infectious diarrhea. We used whole-genome sequencing (WGS) to measure the prevalence and genetic variability of C. difficile at a single hemato-oncology ward over a 10 year period. Methods Between 2008 and 2018, 2077 stool samples were obtained from diarrheal patients hospitalized at the Department of Lymphoma; of these, 618 were positive for toxin A/B. 140 isolates were then subjected to WGS on Ion Torrent PGM sequencer. Results 36 and 104 isolates were recovered from 36 and 46 patients with single and multiple CDIs, respectively. Of these, 131 strains were toxigenic. Toxin gene profiles tcdA(+);tcdB(+);cdtA/cdtB(+) and tcdA(+);tcdB(+);cdtA/cdtB(-) were identified in 122 and nine strains, respectively. No isolates showed reduced susceptibility to metronidazole and vancomycin. All tested strains were resistant to ciprofloxacin, and 72.9%, 42.9%, and 72.9% of strains were resistant to erythromycin, clindamycin, or moxifloxacin, respectively. Multi-locus sequence typing (MLST) identified 23 distinct sequence types (STs) and two unidentified strains. Strains ST1 and ST42 represented 31.4% and 30.1% of all strains tested, respectively. However, while ST1 was detected across nearly all years studied, ST42 was detected only from 2009 to 2011. Conclusions The high proportion of infected patients in 2008–2011 may be explained by the predominance of more transmissible and virulent C. difficile strains. Although this retrospective study was not designed to define outbreaks of C. difficile, the finding that most isolates exhibited high levels of genetic relatedness suggests nosocomial acquisition.